2018
DOI: 10.4274/jtgga.2017.0112
|View full text |Cite
|
Sign up to set email alerts
|

Independent predictors of survival in endometrium cancer: platelet-to-lymphocyte ratio and platelet/neutrophil/monocyte-to-lymphocyte ratio

Abstract: Objective:To evaluate the association between ratios of inflammatory markers and survival in endometrium cancer (EC).Material and Methods:Four hundred ninety-seven patients with epithelial EC were included. The evaluated ratios were neutrophil (N)/lymphocyte (L), neutrophil count divided by the lymphocyte count; platelet (P)/lymphocyte, platelets divided by the lymphocyte count; lymphocyte/monocyte (M), lymphocytes divided by the monocyte count; NM/L, neutrophil plus monocyte divided by the lymphocyte count; P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…OS. Comert et al [13] found that PLR was an independent prognostic marker for OS, but NLR was not a significant indicator. Prognostic values of NLR and PLR in EC are unclear.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 98%
See 3 more Smart Citations
“…OS. Comert et al [13] found that PLR was an independent prognostic marker for OS, but NLR was not a significant indicator. Prognostic values of NLR and PLR in EC are unclear.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 98%
“…Six original papers reported that NLR was an independent predictor for a shortened OS in patients with EC [12,[15][16][17][18][19], while NLR was not identified as a prognostic factor for OS in three studies [13,20,21]. The combined analysis of nine publications showed that the NLR values higher than the cut-off value predicted a worse OS (pHR = 2.22, 95% CI 1.77-2.78, Fig.…”
Section: Correlation Between Nlr and Ec Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophils, monocytes, and lymphocytes are regarded as important elements in both the innate and adaptive immune response, playing a big role in the direct elimination of harmful substances, the secretion and mediation of chemokines and molecules, and the cascade activation of a series of cells and activities. [ 28 , 29 ] Platelets were previously understood as a core element in blood coagulation and thrombus formation process, but presently platelets are also considered to release several kinds of pro-inflammatory or inflammatory molecules which are essential in the cascade reaction. [ 30 ] In other words, besides coagulation, platelets also interact with various elements in the immune systems.…”
Section: Discussionmentioning
confidence: 99%